Burned Ear Reconstruction Using the Combination of an Expanded Postauricular Scar Skin Flap and a Postauricular Fascial Flap - Guo, Peipei; Pan, Bo; Jiang, Haiyue; Yang, Qinghua; Lin, Lin (Facial Plastic Surgery, 2020)
The external ear is highly vulnerable to burn injury due to its location and thin integument. Reconstruction of the external ear after burns is a major challenge to undertake, and surgeons face many problems, including excessive scar tissue, poor blood supply, a paucity of available skin, and a high infection rate, when designing an operative plan for patients with postburn auricular deformity. In this article, the authors describe their experience of using an expanded postauricular scar flap combined with a postauricular fascial flap as the coverage for the framework for subtotal and total ear reconstruction in 27 burned patients. Four patients developed expander exposure and two developed framework exposure, which were resolved with good results after further repair. After an average follow-up time of 6 months, all of the patients experienced very good cosmetic outcomes, high satisfaction, and low morbidity.
Keywords: burn injury; ear reconstruction; postauricular fascial flap; expanded postauricular scar skin flap